Longman's tropical agriculture books available from CTA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Good textbooks on tropical agriculture usually have a high price-tag. This is because they can take several years to produce, as they must be written by eminent persons who have other demands on their time, and because authoritative texts on...